The Antecedents And Consequences Of Customer Purchase Decision In Tokopedia - Jessica Jusup; Margaretha Pink Berlianto (Cakrawala Repositori IMWI, 2023)
The purpose of this study was to determine the effect of brand awareness, brand image, brand love, trust, customer satisfaction, and purchase decisions on repurchase intention in the Tokopedia e-commerce application. The population used in this study were individuals who owned and used the Tokopedia application by distributing questionnaires online to 243 respondents. The sampling technique used in this study was purposive sampling. Data analysis using the PLS-SEM application. The results of this study indicate that brand awareness and brand image have affect on customer satisfaction. Brand image, brand love, and trust affect purchasing decisions, while brand ambassadors has no affect purchasing decisions. Customer satisfaction and purchase decisions affect repurchase intentions.